FABRIKASI DAN PENGUJIAN TELAPAK KAKI PALSU JENIS SINGLE AXIS - Wardoyo, Christianus Pigun; Mahardika, Muslim; Suyitno, Suyitno; Dharmastiti, Rini; Salim, Urip Agus; Arifvianto, Budi (Jurnal Rekayasa Mesin, 2024)
Along with the increasing number of persons with disabilities, the need for prosthetic foot has also increased. However, the irony is that some of the products circulating in Indonesia are still imported from abroad, while the domestic product is quite limited and possesses some drawbacks. This study aims to study the production process of the single axis type of the right-side prosthetic foot as well as to evaluate the performance of this product. The prosthetic foot in this research was made from thermoplastic polyurethane (TPU) resin and prepared with casting by pouring it into a pre-fabricated mold. A single-axis type of right prosthetic product could have been successfully made in this study with men's shoe sizes EU 42 and a mass of 654 g. The result of evaluation of the material and foot prosthetic product showed an average Shore hardness value of 54.3 HA. According to the result of compression test, this prosthetic product was also able withstand the highest compressive load up to 259.76 kgf. Finally, the result of fatigue test showed no damage on the foot prosthetic product until 90.000 cycle.